Peran Pelaku Usaha Mikro Kecil Menengah (UMKM) Opak Jepit dalam Pengembangan Usaha pada Era Digital di Desa Balongmojo, Gresik (Jurnal Simki Economic, 2025)
Researchers want to know about the Role of Micro, Small and Medium Enterprises (MSMEs) of Opak Jepit in the Digital Era in Balongmojo Village, Gresik Regency. The main problem in this study is the development of sales and marketing of Opak Jepit in Balongmojo Village, Gresik Regency which is very lacking, the formulation of the problem in this study is how is the role of micro, small and medium enterprises (MSMEs) in the digital era in Balongmojo Village. The background of this study is the role and efforts of MSME Opak Jepit actors in developing or increasing sales of opak jepit amidst increasingly advanced digital developments. The purpose of this study is to determine the development of MSME Opak Jepit in the current digital era and what efforts have been made by opak jepit producers in competing to market their products amidst digital developments. This study uses a qualitative approach, with the subjects of opak jepit producers in Balongmojo Village, consumers, and village officials. There are 6 (six) informants used in this study. Data were obtained from interviews, observations, and documentation, which were then analyzed qualitatively descriptively. The results of this study show that the development of Opak Jepit in Balongmojo Village has followed digital developments that can make it easier for consumers to recognize and buy Opak Jepit products produced by Balongmojo Village.